Accounting for growing urban-rural welfare gaps in India. (October 2019) - Azam, Mehtabul
Highlights: The urban-rural welfare gap in India in 1983, 1993, 2004, and 2011 is examined across the consumption distribution. Unconditional quantile regression decomposition suggests that urban advantage in endowments accounts for majority of the gap in all four years. The urban-rural gap widened gradually over 1983–2011. Increased gap in share of tertiary educated population accounts for a significant part of the observed increase in the welfare gap over 1983–2011. Abstract: Using data from the large-scale consumption expenditure surveys collected by Indian National Sample Survey Organization, we examine the urban-rural welfare gap in India in 1983, 1993, 2004, and 2011 across the entire consumption distribution. Our main measure of welfare is spatially adjusted per capita consumption expenditure. Using the unconditional quantile regression decomposition, we find that the majority of the observed gap in each year is explained by the urban advantage in endowments. Difference in educational distributions across urban and rural areas explains a significant part of the gap observed in each year. Over time, there has been a gradual widening of the urban-rural gap. A decomposition of the change in the gap over 1983–2011 suggests that increasing gap between urban and rural areas in the share of tertiary educated population accounts for a significant part of the observed increase in the gap.